Fair Weather or Foul? : The Macroeconomic Effects of El Nino - Cashin, Paul (IMF Working Papers; Working Paper ;, 2015)
This paper employs a dynamic multi-country framework to analyze the international macroeconomic transmission of El Nino weather shocks. This framework comprises 21 country/region-specific models, estimated over the period 1979Q2 to 2013Q1, and accounts for not only direct exposures of countries to El Nino shocks but also indirect effects through thirdmarkets. We contribute to the climate-macroeconomy literature by exploiting exogenous variation in El Nino weather events over time, and their impact on different regions crosssectionally, to causatively identify the effects of El Nino shocks on growth, inflation, energy and non-fuel commodity prices. The results show that there are considerable heterogeneities in the responses of different countries to El Nino shocks. While Australia, Chile, Indonesia, India, Japan, New Zealand and South Africa face a short-lived fall in economic activity in response to an El Nino shock, for other countries (including the United States and European region), an El Nino occurrence has a growth-enhancing effect. Furthermore, most countries in our sample experience short-run inflationary pressures as both energy and non-fuel commodity prices increase. Given these findings, macroeconomic policy formulation should take into consideration the likelihood and effects of El Nino weather episodes.